2009
DOI: 10.1126/science.1167768
|View full text |Cite
|
Sign up to set email alerts
|

Neural Mechanisms of a Genome-Wide Supported Psychosis Variant

Abstract: Schizophrenia is a devastating, highly heritable brain disorder of unknown etiology. Recently, the first common genetic variant associated on a genome-wide level with schizophrenia and possibly bipolar disorder was discovered in ZNF804A (rs1344706). We show, by using an imaging genetics approach, that healthy carriers of rs1344706 risk genotypes exhibit no changes in regional activity but pronounced gene dosage-dependent alterations in functional coupling (correlated activity) of dorsolateral prefrontal cortex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

39
343
1
5

Year Published

2009
2009
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 386 publications
(388 citation statements)
references
References 6 publications
39
343
1
5
Order By: Relevance
“…[33][34][35] As expected, we observed significant association of rs2709370 with hippocampal function during memory recall (P<0.01, family wise error corrected for multiple comparisons across the region of interest, Figure 2). The risk allele [C] carriers likewise showed diminished activation of the left hippocampus, consistent with a previous study of patients with BD who showed impaired hippocampal function, further supporting the involvement of CREB1 in BD.…”
Section: Effects Of the Risk Snps On Hippocampal Volumes And Hippocamsupporting
confidence: 84%
See 1 more Smart Citation
“…[33][34][35] As expected, we observed significant association of rs2709370 with hippocampal function during memory recall (P<0.01, family wise error corrected for multiple comparisons across the region of interest, Figure 2). The risk allele [C] carriers likewise showed diminished activation of the left hippocampus, consistent with a previous study of patients with BD who showed impaired hippocampal function, further supporting the involvement of CREB1 in BD.…”
Section: Effects Of the Risk Snps On Hippocampal Volumes And Hippocamsupporting
confidence: 84%
“…30,31 We extracted the association results of CREB1 SNP with bilateral hippocampal volume instead of single-side hippocampal volume from these two GWASs, because the volumes of the right and left hippocampus do not differ significantly in healthy subjects, 31 and the genetic bases are likely the same. 32 For brain functions, we analyzed the data of a German sample of healthy individuals (N = 279) that was part of an ongoing study on neurogenetic mechanisms of psychiatric disease to study the effects of risk CREB1 SNPs on hippocampal function, [33][34][35] using blood oxygenation level-dependent functional magnetic resonance imaging measurement during three consecutive blocks of memory tasks (that is, encoding, recall and recognition of faceprofession pairs). We analyzed the effects of the SNPs on right and left hippocampal function separately, assuming potential asymmetry in hippocampal function, with the right hippocampus supporting processes contributing to visuo-spatial memory and the left hippocampus to verbal/narrative or episodic memory.…”
Section: Analysis Of Hippocampal Volume Hippocampal Function and Cogmentioning
confidence: 99%
“…Subjects (n= 122) were drawn from an ongoing large-scale multicenter imaging genetics study 18 (Esslinger et al plus 7 subsequently scanned subjects) that is being conducted at two sites in Mannheim and Bonn, Germany. All participants were healthy German volunteers with parents and grandparents of European origin.…”
Section: Sample Ascertainment and Selection For The Imaging Genetics mentioning
confidence: 99%
“…One group took 115 healthy people, a little less than half of whom had two copies of the high-risk ZNF804A variant, and compared their brain activity using functional magnetic resonance imaging (fMRI), a method that reveals local blood oxygenation and presumably electrical activity in the brain in real time. Those with the variant, they found, had abnormal connectivity between certain brain areas, impairing "the degree in which they talk to one another", says Andreas Meyer-Lindenberg, the director of the Central Institute of Mental Health in Mannheim, Germany, who led the study 6 . Healthy adults with the variant were showing schizophrenia-like brain activity even though they showed no outward signs of disease.…”
Section: Scoping Schizophreniamentioning
confidence: 99%